Veiksmažodžio kintamojo centro šaknų struktūra - Kruopienė, Irena (Kalbotyra, 2002)
The article presents a structural analysis of roots with an alternating nucleus in which various vowel changes occur, e. g. gẽria – gė́rė, gérti ‘to drink’, ker̃pa – kir̃po, kir̃pti ‘to cut’, žū̃va – žùvo, žū́ti ‘to die’. The automatic changes of vowels (which depend on the phonemic structure of root) are more frequent then the inherited (the oldest) ones. In the position of the alternating nucleus of the root only short vowels [a], [e], [i], [u] occur, the most productive of them being the vowel [e]. A more important role in the root is played by final two-member consonant clusters. All alternating nuclear roots are represented by seven patterns in modern Lithuanian.